Single dose primaquine for clearance of Plasmodium falciparum gametocytes in children with uncomplicated malaria in Uganda: a randomised, controlled, double-blind, dose-ranging trial. - Eziefula, A; Bousema, T; Yeung, S; Kamya, M; Owaraganise, A; Gabagaya, G; Bradley, J; Grignard, L; Lanke, K; Wanzira, H; Mpimbaza, A; Nsobya, S; et al. (Elsevier, 2014)
BACKGROUND: Primaquine is the only available drug that clears mature Plasmodium falciparum gametocytes in infected human hosts, thereby preventing transmission of malaria to mosquitoes. However, concerns about dose-dependent haemolysis in people with glucose-6-phosphate dehydrogenase (G6PD) deficiencies have limited its use. We assessed the dose-response association of single-dose primaquine for gametocyte clearance and for safety in P falciparum malaria. METHODS: We undertook this randomised, double-blind, placebo-controlled trial with four parallel groups in Jinja district, eastern Uganda. We randomly allocated Ugandan children aged 1-10 years with uncomplicated falciparum malaria and normal G6PD enzyme function to receive artemether-lumefantrine, combined with either placebo or with 0.1 mg/kg, 0.4 mg/kg, or 0.75 mg/kg (WHO reference dose) primaquine base. Randomisation was done with computer-generated four-digit treatment assignment codes allocated to random dose groups in block sizes of 16. Study staff who provided care or assessed outcomes and the participants remained masked to the intervention group after assignment. The primary efficacy endpoint was the non-inferiority of the mean duration of gametocyte carriage in the test doses compared with the reference group of 0.75 mg primaquine per kg, with a non-inferiority margin of 2.5 days. The primary safety endpoint was the superiority of the arithmetic mean maximum decrease in haemoglobin concentration from enrolment to day 28 of follow-up in the primaquine treatment groups compared with placebo, with use of significance testing of pairwise comparisons with a cutoff of p=0.05. The trial is registered with ClinicalTrials.gov, number NCT01365598. FINDINGS: We randomly allocated 468 participants to receive artemether-lumefantrine combined with placebo (119 children) or with 0.1 mg/kg (116), 0.4 mg/kg (116), or 0.75 mg/kg (117) primaquine base. The mean duration of gametocyte carriage was 6.6 days (95% CI 5.3-7.8) in the 0.75 mg/kg reference group, 6.3 days (5.1-7.5) in the 0.4 mg/kg primaquine group (p=0.74), 8.0 days (6.6-9.4) in the 0.1 mg/kg primaquine group (p=0.14), and 12.4 days (9.9-15.0) in the placebo group (p<0.0001). No children showed evidence of treatment-related haemolysis, and the mean maximum decrease in haemoglobin concentration was not associated with the dose of primaquine received-it did not differ significantly compared with placebo (10.7 g/L, SD 11.1) in the 0.1 mg/kg (11.4 g/L, 9.4; p=0.61), 0.4 mg/kg (11.3 g/L, 10.0; p=0.67), or 0.75 mg/kg (12.7 g/L, 8.2; p=0.11) primaquine groups. INTERPRETATION: We conclude that 0.4 mg/kg primaquine has similar gametocytocidal efficacy to the reference 0.75 mg/kg primaquine dose, but a dose of 0.1 mg/kg was inconclusive for non-inferiority. Our findings call for the prioritisation of further trials into the efficacy and safety of doses of primaquine between 0.1 mg/kg and 0.4 mg/kg (including the dose of 0.25 mg/kg recently recommended by WHO), in view of the potential for widespread use of the drug to block malaria transmission. FUNDING: Wellcome Trust and the Bill and Melinda Gates Foundation.